Selectin binding is essential for peritoneal carcinomatosis in a xenograft model of human pancreatic adenocarcinoma in pfp−−/rag2−− mice. Issue 5 (5th April 2012) - Gebauer, Florian; Wicklein, Daniel; Stübke, Katrin; Nehmann, Nina; Schmidt, Anna; Salamon, Johannes; Peldschus, Kersten; Nentwich, Michael Fabian; Adam, Gerhard; Tolstonog, Genrich; Bockhorn, Maximilian; Izbicki, Jakob R; et al.
Abstract : Background and objective: E- and P-selectins expressed on the luminal surface of mesodermally derived endothelial cells play a crucial role in the formation of haematogenous metastases in a number of malignancies. As peritoneal mesothelial cells are also derived form the mesoderm, it was hypothesised that selectins are also of importance in peritoneal tumour spread. Methods: Immunohistochemistry was used to identify selectin expression on normal human peritoneum and isolated mesothelial cells. E- and P-selectin interactions with human pancreatic adenocarcinoma cells were investigated in dynamic flow assays and flow cytometry; the latter was also used to determine the main selectin ligands on pancreatic adenocarcinoma cell lines PaCa 5061, BxPC-3 and PaCa 5072, and selectin expression on human mesothelial cells. All cell lines were xenografted into the peritoneum of E- and P-selectin-deficient pfp/rag2 mice and selectin wild-type controls. Peritoneal carcinomatosis was quantified using MRI or a scoring system. Results: E- and P-selectin were constitutively expressed on human mesothelial and endothelial cells in the peritoneum. PaCa 5061 and BxPC-3 cells interacted with E- and P-selectins in dynamic flow assays and flow cytometry, with CA19-9 (Sialyl Lewis a) being the main E-selectin ligand. For xenografted PaCa 5061 and BxPC-3 cells, peritoneal metastasis was significantly reduced in E- and P-selectin double knockout mice compared with wild-type pfp/rag2 animals. In contrast, PaCa 5072 cells were almost devoid of selectin binding sites and no intraperitoneal tumour growth was observed. Conclusion: Interactions of tumour cells with peritoneal selectins play an important role in the peritoneal spread of pancreatic adenocarcinoma.